Scythe & sparrow eaudiobook - Weaver, Brynne (Ruinous Love Trilogy, 2025)
From the #1 New York Times and USA TODAY bestselling author of the genre-breaking international TikTok sensation Butcher & Blackbird and Leather & Lark comes the final book in the Ruinous Love Trilogy—a friends-with-benefits dark romantic comedy packed with murder, mayhem, and spice. Doctor Fionn Kane is running from a broken heart, one he hopes to mend in small-town Nebraska, far away from his almost-fiancé and his derailed surgical career. It's a simpler life: head down, hard work, and absolutely no romantic relationships. He wants none of the circus he left behind in Boston. But then the real circus finds him. Motorcycle performer Rose Evans has spent a decade on the road with the Silveria Circus, and it suits her just fine, especially when she has the urge to indulge in a little murder when she's not in the spotlight. But when a kill goes awry and she ends up with an injured leg, Rose finds herself stuck in Nebraska, at the home of the adorably nerdy town doctor. The problem is, not every broken heart can be sewn back together. . . . And the longer you stay in one place, the more likely your ghosts are to catch up.